PENYULUHAN PENTINGNYA MENGENALKAN DAN MEMPERAKTEKKAN TATACARA BERWUDHU YANG BENAR PADA SISWA-SISWI TK PWP II PERTAMINA PLAJU (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2022)
Thaharah according to language means clean and holy, according to the term (fiqj experts) it means to clean oneself from hadast or unclean things such as bathing, ablution and tayamum. While ablution is one of the purification of small hadast before praying. The wahib ablution command did come down at the same time as the obligatory prayer command, approximately one year and a half before the hijri year (Q.S Almaidah verse 6). And the Messenger of Allah said,